Gender‐Based Cyberviolence Prevention in European Secondary Education: A Scoping Review on the Intersection Between Comprehensive Sexuality Education and Digital Literacy - Valeria Piras; Arpita Chakraborty (Journal of School Health, 2026)
ABSTRACT Background The increasing pervasiveness of digital technologies in adolescent life has heightened concerns about gender‐based cyberviolence, especially toward girls, LGBTQI+ youth, and other marginalized groups. While European Union (EU) policy, including Directive (EU) 2024/1385, recognizes these harms, formal education systems in EU Member States lack integrated strategies that connect Comprehensive Sexuality Education (CSE) and Digital Literacy (DL). Methods This scoping review explores how academic research addresses this intersection in secondary education, drawing on 14 peer‐reviewed studies published between 2014 and 2025 and sourced from Scopus, Web of Science, and Research Rabbit. Findings The review reveals a fragmented field: CSE and DL are often treated in isolation, and cyberviolence prevention is rarely included. Young people's perspectives remain largely absent. Implications for School Health Policy, Practice, and Equity These gaps highlight a misalignment between policy ambitions and educational practices. This review offers insight into how health education initiatives in schools can be reoriented to better integrate comprehensive sexuality education and digital literacy, thereby contributing to the prevention of gender‐based online harm. Conclusions Integrating CSE and DL in secondary schools is essential to support more equitable, policy‐aligned, and effective prevention of gender‐based cyberviolence among adolescents.